Green Synthesis, in-vitro Antimicrobial Evaluation, Docking, and SAR Studies of Potent Quinoline-4-Carboxylic Acids - Pallavi, Badvel; Singh, Rajnish P.; Jha, Prabhat Nath; Chander, Subhash; Murugesan, Sankaranarayanan; Sharma, Prachi; Shukla, Paritosh (Letters in Organic Chemistry, 2019)
The paper describes the synthesis of quinoline-4-carboxylic acid derivatives employing completely green methods such as the use of water as solvent and of microwave irradiation for heating. The prepared molecules were examined for bactericidal and antifungal behavior and two of the tested compounds showed reasonably good antimicrobial activity. The biological activity results were further corroborated by fluorescence microscopy and by evaluating their time-dependent bactericidal behavior. Two of the most potent compounds were then subjected to docking against DNA gyrase protein (PDB ID: 2XCT) showing possible interactions responsible for the potency of these compounds. Also, an SAR analysis was proposed based on the results obtained.
Keywords: Quinoline-4-carboxylic acids